Dietary intake in Japanese patients with type 2 diabetes: Analysis from Japan Diabetes Complications Study. Issue 2 (1st December 2013) - Horikawa, Chika; Yoshimura, Yukio; Kamada, Chiemi; Tanaka, Shiro; Tanaka, Sachiko; Takahashi, Akane; Hanyu, Osamu; Araki, Atsushi; Ito, Hideki; Tanaka, Akira; Ohashi, Yasuo; Akanuma, Yasuo; et al.
Abstract Aims/Introduction Though there are many differences in dietary habits and in the metabolic basis between Western and Asian people, the actual dietary intake in Asian patients with diabetes has not been investigated in a nationwide setting, unlike in Western countries. We aimed to clarify dietary intake among Japanese individuals with type 2 diabetes, and identify differences in dietary intake between Japanese and Western diabetic patients. Materials and Methods Nutritional and food intakes were surveyed and analyzed in 1, 516 patients with type 2 diabetes aged 40–70 years from outpatient clinics in 59 university and general hospitals using the food frequency questionnaire based on food groups (FFQg). Results Mean energy intake for all participants was 1737 ± 412 kcal/day, and mean proportions of total protein, fat, and carbohydrate comprising total energy intake were 15.7, 27.6 and 53.6%, respectively. They consumed a 'low‐fat energy‐restricted diet' compared with Western diabetic patients, and the proportion of fat consumption was within the suggested range that has been traditionally recommended in Western countries. As a protein source, consumption of fish (100 g) and soybean products (71 g) was larger than that of meat (50 g) and eggs (29 g). These results imply that dietary content and food patterns among Japanese patients with type 2 diabetes are quite close to those reported as suitable for prevention of obesity, type 2 diabetes, cardiovascular disease, and total mortality in Europe and America. Conclusions A large difference was shown between dietary intake by Japanese and Western patients. These differences are important to establish ethnic‐specific medical nutrition therapy for diabetes.